Enhancing Digital Literacy through Editorial Text Reading Materials for Vocational High School Students - Nur Rohmawati; Miftahulkhairah Anwar; Sintowati Rini Utami (AL-ISHLAH: Jurnal Pendidikan, 2024)
Teaching materials play a vital role in achieving learning objectives. However, the editorial text teaching materials used at SMK Ksatrya for Phase F do not meet students' needs, particularly for Indonesian language outcomes related to reading. Existing materials are less relevant to learning goals and technological advancements, prompting the need for digital literacy-based materials incorporating text and video that are accessible and adaptable to diverse learning environments. This study employed the Borg and Gall development model, which involves steps such as research and information collection, planning, product development, field testing, operational field testing, final revisions, and dissemination. Data were collected through validation processes and limited field testing. Digital literacy-based editorial text teaching materials were developed and validated by material experts, media experts, and Indonesian language teachers. Validation covered aspects such as content quality, presentation, language, readability, graphics, software engineering, visual design, and application features. Field testing with 36 students confirmed the materials' suitability with minor revisions addressing accessibility issues. The teaching materials effectively address students' needs by combining editorial texts with digital resources to enhance literacy and critical thinking skills. The inclusion of text and video supports diverse learning preferences, while the use of digital platforms ensures accessibility and modern relevance. Digital literacy-based teaching materials for editorial text reading are practical and impactful, fostering reading proficiency, digital literacy, and critical thinking among SMK Ksatrya students. These materials represent a significant advancement in aligning learning tools with technological and educational needs.